ANALYSIS OF SANGKURIANG CATFISH ( Clarias garipinus) FARMING BUSINESS IN SEMPAJA BARAT SUB-DISTRIC SAMARINDA CITY (CASE STUDY ON LELE GREEN BUSINESS): ANALISIS USAHA BUDIDAYA KOLAM TERPAL IKAN LELE SANGKURIANG (Clarias garipinus) DI KELURAHAN SEMPAJA BARAT KOTA SAMARINDA (STUDI KASUS PADA USAHA LELE GREEN) - FERONIKA AGATHA MANALU, FERONIKA AGATHA MANALU; Haqiqiansyah, Gusti; Fahrizal, Wahyu (2339-1324, 2024)
This study aimed to find out the profit and the feasibility of the Sangkuriang catfish farming business based on the following indicators: RCR, BEP (production, price, and sales), Payback Period. This study was conducted in Sempaja Barat Sub-Distric, Samarinda City. The sampling method is a case study which is an approach that aims to provide a detailed description of the object under study. The result showed that the total profit was IDR 22,433,517/production. The Sangkuriang catfish farming business, based on the RCR, BEP, Payback Period, is feasible to be maintained.